Application of Probiotics in Various Preparations in Fish Farming - Mumtaz, Amalia; Andriani, Yuli; Nurhayati, Atikah; Zidni, Irfan (Fakultas Perikanan dan Kelautan Universitas Riau, 2025)
Fish farming plays a vital role in providing animal protein. Increased production is often hampered by declining water quality, disease, and excessive use of chemicals. The application of probiotics in various preparations is an environmentally friendly alternative to increase production efficiency while maintaining the balance of aquatic ecosystems. This study aimed to examine the effectiveness of probiotic applications in various preparations in fish farming activities. The method used was a literature study. The results of the study showed that probiotics, such as lactic acid bacteria, Bacillus sp., B. subtilis, B. megaterium, Lactobacillus sp, L. casei and Saccharomyces cerevisiae have a positive impact on growth, feed efficiency, endurance, and water quality. Feed quality, environmental conditions, dosage and method of administration, suitability of probiotic strains, and cultivation management influence the effectiveness of probiotics. Selection of the proper preparation and dosage and optimal management of the cultivation environment are the keys to maximizing the benefits of probiotics in increasing productivity and sustainability of fish farming businesses